Israel : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The methodologies used in this paper suggest that Israel's real exchange rate is moderately undervalued, while gains in external competitiveness appear to have been eroded in recent years. Market-based indicators provide a useful additional dimension to the analysis of financial stability in Israel. The Israeli government has made far-reaching reforms to financial markets in recent years. Banks' performance and financial strength have been improving. This paper proposes two rules that are based on a debt-brake concept and an alternative error-correction-mechanism toward fiscal policy in Israel.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet